3 (x – 3) = 5 (2x + 1)
Answers
Answered by
0
Answer:
please mark me as brilliant this is the correct answer
Attachments:
![](https://hi-static.z-dn.net/files/de8/27ce4b8a449e783e0db40ca965e57c22.jpg)
Answered by
10
Answer:
3x - 9 = 10x + 5
3x - 10x = 5 + 9
-7x = 14
-x =
x= -2 ✅
❤MissVolcano❤
Similar questions
English,
1 month ago
Math,
1 month ago
History,
1 month ago
English,
3 months ago
Biology,
3 months ago
Chemistry,
11 months ago
Computer Science,
11 months ago
Environmental Sciences,
11 months ago